New analytical model to generalize the barcelona test using axial displacement - Pujadas, Pablo; Blanco, Ana; Cavalaro, Sergio; Fuente, Albert de la; Aguado, Antonio (Journal of Civil Engineering and Management, 2013)
The Barcelona Test has proved to be very suitable for the systematic control of the tensile properties of Fibre Reinforced Concrete (FRC). Nevertheless, the need to measure the total circumferential opening displacement (TCOD) of the specimen entails the use of an expensive circumferential extensometer. In order to simplify the test, studies from the literature propose the use of the axial displacement of the press (δ) instead of the TCOD, obtaining empirical equations to correlate the energy estimated with both measurements. However, these equations are only valid for δ ranging from 1 to 4 mm and were adjusted based on the test results of just a few types of FRC. The verification of this formulation for other types of FRC shows an average error of 51.1%, thus limiting the simplification proposed for the test. In this paper, a new analytical model to convert the δ into the TCOD is developed and validated for a wide range of FRC. Besides being applicable to the whole range of δ, the new model provides a clear physical understanding of the main mechanism observed during the test and shows an average error of only 6.7%, making it possible to simplify the Barcelona test.